Larvicidal effect of disinfectant soap on Anopheles gambiae s.s (Diptera: Culicidae) in laboratory and semifield environs - Mdoe, France P; Nkwengulila, Gamba; Chobu, Mariam; Lyaruu, Lucile; Gyunda, Israel L; Mbepera, Saada; Xue, Rui-De; Kweka, Eliningaya J (My University, 2014)
Abstract Background Mosquito larval control using chemicals and biological agents is of paramount importance in vector population and disease incidence reduction. A commercial synthetic disinfectant soap was evaluated against larvae of Anopheles gambiae s.s. in both laboratory and semi field conditions. Method Five concentrations of commercial synthetic disinfectant soap (0.0001, 0.001, 0.01, 0.1 and 1%) were prepared and evaluated against third instar larvae in laboratory and semi field environments. Mortality was scored at 12, 24, 48, and 72and#160;hrs. Each dosage had 6 replicates, having twenty 3rd instar larvae of An.gambiae s.s. Results In the laboratory phase, all dosages had significantly higher larval mortalities than in controls, while in semi field conditions, the dosages of 0.0001, 0.001 and 0.01% had lower mortalities than laboratory trials. In the comparison between semi field and laboratory trials, only 0.1 and 1% dosage had significant difference with more mortality in semifield conditions. Proportions of larvae that died during mortality monitoring intervals in laboratory and semi field had significant differences only at 12and#160;hrs and 72and#160;hrs. Conclusion The findings of this study have demonstrated that the mortality of larvae caused by commercial synthetic disinfectant soap is worth further studies in open water bodies. More studies are necessary to find out the effect of sunlight on the chemistry of the synthetic disinfectant and other variables in small scale full field trials.